2012
DOI: 10.1364/josaa.29.002092
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor cavity metrology

Abstract: Long-baseline laser interferometers used for gravitational-wave detection have proven to be very complicated to control. In order to have sufficient sensitivity to astrophysical gravitational waves, a set of multiple coupled optical cavities comprising the interferometer must be brought into resonance with the laser field. A set of multi-input, multi-output servos then lock these cavities into place via feedback control. This procedure, known as lock acquisition, has proven to be a vexing problem and has reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The obvious correlated mechanisms (temperature and intensity noise coupling) are likely insignificant compared to this as discussed in section 3. This is low enough to not limit the lock acquisition [9,10] scheme for Advanced LIGO and other gravitational-wave detectors. Additionally, we have shown that there is no excess noise process at a level which is of interest to those doing precision atomic spectroscopy [7], using frequency combs to transfer optical harmonics [4,5,21] and other tests of fundamental physics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obvious correlated mechanisms (temperature and intensity noise coupling) are likely insignificant compared to this as discussed in section 3. This is low enough to not limit the lock acquisition [9,10] scheme for Advanced LIGO and other gravitational-wave detectors. Additionally, we have shown that there is no excess noise process at a level which is of interest to those doing precision atomic spectroscopy [7], using frequency combs to transfer optical harmonics [4,5,21] and other tests of fundamental physics.…”
Section: Discussionmentioning
confidence: 99%
“…In order to simplify this problem, auxiliary fields will be generated by SHG and used to form independent signals for two of the cavities. This technique is being developed using some small scale prototypes [9,10]. To understand the limits of such a scheme, we need to bound the frequency noise introduced in the second harmonic generation process.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of each is independently locked to one of the arm cavities with a control bandwidth of several kilohertz. Therefore, the frequency fluctuations of each green laser are proportional to the length fluctuations of the corresponding arm cavity through the relation Δν g =ν g ≈ ΔL=L, where ν g is the frequency of either of the auxiliary lasers [39]. Beams from these two lasers are interfered and measured on a photodetector, producing a beat-note close to 158 MHz.…”
Section: Calibration Via Radio-frequency Oscillatormentioning
confidence: 99%
“…Moreover, the effective actuator force can be smaller than the aforementioned value for fast signals due to the frequency response of the electronics and can therefore further deteriorate lock acquisition. Several approaches have been proposed to make lock acquisition less stochastic [7][8][9][10][11]. An intriguing approach among them is guided lock, which virtually increases the signal range ΔL max by extrapolating the motion of the cavity [12].…”
Section: Introductionmentioning
confidence: 99%